The Effect Of The Small Side Game Method On Futsal Passing In The Extracurricular Activities Of The Dehasen University Of Bengkulu - Ramadhoni, Nanda Rahmat (Journal of Physical Education and Sports, 2025)
This study aims to evaluate the effectiveness of small side game training in improving futsal players' passing techniques. This study is an experimental study. This study uses a pre-experimental design which is a development method of one group pretest-postent design. The population of this study was all students who participated in the Himajas Unived Bengkulu futsal extracurricular, totaling 20 students. This can be seen from the average increase in skills in 30 seconds of passing and stopping to the wall for each implementation through initial test data (pre-test) and final data (post-test). Initial test (pre test) with the highest score of 90, the lowest score of 60 with an average of 76.00. Final test (post test) with the highest score of 100, the lowest score of 80 and an average of 91.50. Initial test 76.00 increased to final test 91.50. The results of the analysis obtained t count -9.131 is in the rejection area Ho t table 100 is in the rejection area Ho then Ha can be accepted there is an influence of the small side game method on futsal passing in the Himajas extracurricular at Dehasen University Bengkulu. It can be concluded that there is an influence of the small side game method on futsal passing in the Himajas extracurricular at Dehasen University Bengkulu.